The Influence of Halal Certification and Standardization on Product Innovation of Food and Beverage MSMEs in the Sharia Tourism Park of Pamah Semelir, Langkat Regency, North Sumatra - Masditou, Masditou (Lembaga Pengembangan Kinerja Dosen, 2025)
In the face of growing global competition and changing consumer preferences, product innovation has become essential for success and growth in the food and beverage sector. Halal certification and standardization can play significant roles in driving innovation by motivating micro, small, and medium enterprises (MSMEs). Halal certification encourages MSMEs to develop products that adhere to halal standards, while standardization offers a regulatory framework that can influence creativity and flexibility in the innovation process. This research explores the impact of halal certification and standardization on product innovation within food and beverage MSMEs located in the Sharia Tourism Park of Langkat Regency. Using a quantitative approach with a positivist paradigm, the study employs purposive sampling to collect data through questionnaires. The study population consists of 89 MSMEs in the food and beverage sector operating within the Sharia Tourism Park, all meeting specific criteria. The data was processed and analyzed using SPSS software. The study's findings reveal that the hypothesis regarding halal certification (X1) was rejected, as the t-calculated value was smaller than the t-table value, indicating that other factors may influence product innovation. Conversely, the hypothesis for halal standardization (X2) was accepted, as the t-calculated value exceeded the t-table value, demonstrating a significant effect of halal standardization on product innovation. Additionally, the F-test results show that both halal certification and standardization together significantly affect product innovation in the MSMEs of Langkat Regency's Sharia Tourism Park.